2016
DOI: 10.1080/14992027.2016.1211763
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the characteristics of persistent postural-perceptual dizziness: A clinical-based study in China

Abstract: In this sample we showed that PPPD was more represented in female patients, the age of onset was 40-60 years old, the majority of patients had sleep disorders, anxiety was the main mood disorder to be identified, and personality analysis found that neurotic personality may be the risk factor for developing PPPD. Further large scale studies are suggested in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 17 publications
9
37
2
1
Order By: Relevance
“…Patients with CSD also showed reduced connectivity between the left anterior insula/inferior frontal gyrus and right middle occipital cortex, left anterior cingulate cortex and right superior temporal gyrus, and left hippocampus and right superior temporal gyrus. In sum, the two imaging studies in normal individuals were consistent with preceding psychological investigations of CSD (Chiarella et al, ; Staab, Rohe, Eggers, & Shepard, ) and PPPD (Yan et al, ) and suggested that anxiety‐related personality traits increase the sensitivity of vestibular, visual, and anxiety regions of the brain to vestibular and visual motion stimuli and increase their connectivity with one another in a manner that may enhance responses to visual over vestibular inputs. The imaging studies of patients with visually induced dizziness and CSD were consistent with previous psychophysiological studies of patients with persistent dizziness (Cousins et al, ) and more strongly indicated that a shift to reliance on visual versus vestibular information occurs in patients with PPPD.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Patients with CSD also showed reduced connectivity between the left anterior insula/inferior frontal gyrus and right middle occipital cortex, left anterior cingulate cortex and right superior temporal gyrus, and left hippocampus and right superior temporal gyrus. In sum, the two imaging studies in normal individuals were consistent with preceding psychological investigations of CSD (Chiarella et al, ; Staab, Rohe, Eggers, & Shepard, ) and PPPD (Yan et al, ) and suggested that anxiety‐related personality traits increase the sensitivity of vestibular, visual, and anxiety regions of the brain to vestibular and visual motion stimuli and increase their connectivity with one another in a manner that may enhance responses to visual over vestibular inputs. The imaging studies of patients with visually induced dizziness and CSD were consistent with previous psychophysiological studies of patients with persistent dizziness (Cousins et al, ) and more strongly indicated that a shift to reliance on visual versus vestibular information occurs in patients with PPPD.…”
Section: Introductionsupporting
confidence: 84%
“…This is consistent with the increased connectivity between these areas identified in our patients with PPPD in the analyses that did not control for psychiatric state. It is well established that the anxiety‐related personality trait of neuroticism is a risk factor for PPPD (Chiarella et al, ; Staab et al, ; Yan et al, ). In an fMRI study of normal individuals, neuroticism correlated with increased activity in the visual cortex and with increased connectivity between the visual and frontal cortices, suggesting that neuroticism and state anxiety may mediate the shift to visual dependence in patients with PPPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies using formal psychometric measures found that individuals with the anxiety-related personality traits of neuroticism and introversion [76] had an increased risk for CSD. High neuroticism also was identified in a report on PPPD [100]. In contrast, persons demonstrating resilience, optimism, and beliefs that life is meaningful and manageable had a reduced risk of persistent dizziness after acute vestibular events [85].…”
Section: Possible Risk Factorsmentioning
confidence: 96%
“…Disability varied widely from individuals who had few limitations in daily functioning to those who were severely impaired and unable to work. The average age of patients presenting for evaluation of PPV, CSD, and PPPD is the mid-40 s, with a range from adolescence to late adulthood [10,79,100]. A female predominance has been reported in the first clinical reports on PPPD [10,100].…”
Section: Estimates Of the Prevalence Of Pppdmentioning
confidence: 99%